An upright graphitized carbon material, a method for preparing the same, and a battery application thereof
Patent Information
- Application Number
- CN202410744075.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-06-11
AI Technical Summary
The limited availability of carbon materials in existing dual-ion batteries restricts their application, and the limited resources of lithium-ion batteries limit their application in large-scale energy storage.
Vertical graphitized carbon materials were prepared using microwave plasma chemical vapor deposition. Through alternating carbon deposition and etching processes, two-dimensional vertical graphitized carbon materials with large interlayer spacing were formed for use in battery cathodes, reducing carrier transport paths and improving kinetic performance.
It improves the battery's fast charging performance and long cycle life, avoids the introduction of inactive conductive agents and binders, has low substrate contact resistance, and improves energy density and kinetic performance.
Smart Images

Figure CN118771368B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials technology, specifically relating to an upright graphitized carbon material, its preparation method, and its battery application. Background Technology
[0002] Lithium-ion batteries, with their high energy density and long cycle life, have captured a significant market share in portable electronic devices and electric vehicles. However, the limited and uneven distribution of resources such as cobalt and nickel restricts their application in large-scale energy storage. Therefore, developing new and efficient energy storage technologies is essential. Dual-ion batteries are a novel type of energy storage device that utilizes the synergistic action of cations and anions for energy storage. They typically employ graphite-based carbon materials as the positive electrode, which are abundant in resources, offer a diverse range of intercalable ions, and have high anion intercalation potentials. This results in advantages such as high operating voltage, low cost, and environmental friendliness. However, the carbon materials currently used in dual-ion batteries are relatively limited, which to some extent hinders their application. Summary of the Invention
[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a method for preparing a novel upright graphitized carbon material, which, when used in a dual-ion battery, exhibits good battery stability.
[0004] This invention also proposes an upright graphitized carbon material.
[0005] The present invention also proposes a battery positive electrode.
[0006] The present invention also proposes a battery.
[0007] The present invention also proposes an electrical device.
[0008] In a first aspect, the present invention provides a method for preparing an upright graphitized carbon material, comprising the following steps: preparing an upright carbon material by carbon deposition using microwave plasma chemical vapor deposition, then etching the upright carbon material using an etching gas containing oxygen, and repeating the carbon deposition and etching processes to obtain the upright graphitized carbon material.
[0009] The method for preparing upright graphitized carbon materials according to embodiments of the present invention has at least the following beneficial effects:
[0010] In this invention, upright carbon materials are prepared by carbon deposition using microwave plasma chemical vapor deposition (MPCVD). The upright carbon materials are then etched using an oxygen-containing etching gas. This process is repeated several times (e.g., more than 0 times) on the surface of the resulting material to obtain the upright graphitized carbon material. Specifically, this invention uses MCVD to grow two-dimensional upright graphitized carbon materials in situ on a substrate (which can serve as a positive electrode current collector). The graphitized carbon materials have large interlayer spacing. The etching gas etches the disordered carbon in the upright carbon materials and introduces oxygen defects. Large-sized oxygen replaces graphite carbon, expanding the local space and widening the interlayer spacing, ultimately resulting in a two-dimensional upright graphitized carbon material with a large interlayer spacing. When this two-dimensional upright graphitized carbon material is used in a battery positive electrode, the vertical open structure of the two-dimensional upright graphitized carbon material can directionally guide the transport of anions and electrons by reducing the lengthy carrier transport path, thereby improving mass and charge transfer dynamics. Furthermore, the upright graphitized carbon material possesses a large interlayer spacing and an ordered spatial structure. The large interlayer spacing can reduce the anion diffusion barrier, further improving kinetic performance and enabling fast charging of the battery. The ordered spatial structure can accommodate anion intercalation and expansion, enhancing structural stability and achieving long cycle life of the battery. Moreover, the two-dimensional upright graphitized carbon material in this invention can be combined with a conductive substrate as the positive electrode of the battery, which not only avoids the introduction of inactive conductive agents and binders, thus facilitating high energy density, but also has the advantage of low substrate contact resistance, improving kinetic performance.
[0011] This invention employs microwave plasma chemical vapor deposition (MSCVD) for carbon deposition. Because this technique involves electrodeless discharge and produces pure plasma, while the microwave discharge region is concentrated and does not expand, it can activate and generate various atomic groups such as atomic hydrogen. The maximum kinetic energy of the generated ions is low, preventing corrosion of the existing products. Furthermore, it can produce large-area, stable plasma spheres, making it suitable for preparing large-area carbon materials. The resulting carbon materials exhibit good uniformity, high purity, and good crystal morphology, demonstrating promising application prospects.
[0012] In some embodiments of the present invention, the upright graphitized carbon material is a two-dimensional upright graphitized carbon material.
[0013] In some embodiments of the present invention, the process of the first carbon deposition and the process of subsequent repeated carbon deposition can be the same or different.
[0014] In some embodiments of the present invention, the first etching process and the subsequent repeated etching processes may be the same or different.
[0015] In some embodiments of the present invention, the preparation method includes the following steps:
[0016] S1, using raw material I containing a gaseous carbon source, vertical carbon materials are prepared by carbon deposition on the substrate surface through microwave plasma chemical vapor deposition.
[0017] S2, the upright carbon material is subjected to plasma etching treatment using etching gas;
[0018] S3. Repeat steps S1 and S2 to obtain the two-dimensional upright graphitized carbon material.
[0019] In some embodiments of the present invention, the gaseous carbon source includes at least one of methane, ethylene, acetylene, or carbon dioxide.
[0020] In some embodiments of the present invention, the raw material I for preparation further includes hydrogen.
[0021] In some embodiments of the present invention, in step S1 and / or step S3, during the carbon deposition process, the inlet gas flow ratio of hydrogen to gaseous carbon source is 200:(1-300), such as 200:(50-200), 200:(50-150), etc., specifically such as 200:50, 200:100, 200:150, 100:100, etc.
[0022] In some embodiments of the present invention, during the carbon deposition process in step S1 and / or step S3, the flow rate of hydrogen is 50 to 300 sccm.
[0023] In some embodiments of the present invention, during the carbon deposition process in step S1 and / or step S3, the flow rate of the gaseous carbon source is 10 to 300 sccm.
[0024] In some embodiments of the present invention, during the preparation of the upright carbon material in step S1 and / or step S3, the microwave power is 3 to 15 kW, such as 5.4 to 15 kW, 5.4 to 6.6 kW, etc. More specifically, it can be 5.2 kW, 5.8 kW, 6.4 kW, 7.2 kW, etc.
[0025] In some embodiments of the present invention, during the preparation of the vertical carbon material in step S1 and / or step S3, the growth temperature of the vertical carbon material is 400-1100℃, such as 600-900℃, 800-900℃, etc.
[0026] In some embodiments of the present invention, during the preparation of the upright carbon material in step S1 and / or step S3, the growth pressure of the upright carbon material is 2 to 12 kPa, which may be selected as 5 to 8 kPa, and specifically, may be selected as 6 to 8 kPa.
[0027] In some embodiments of the present invention, in step S1 and / or step S3, the growth time of the upright carbon material during the preparation process is 2 to 200 min, such as 10 to 60 min, specifically 30 to 60 min.
[0028] In this invention, gaseous carbon source and hydrogen are introduced into the cavity used for vapor deposition. The flow rates of the gaseous carbon source and hydrogen, the ratio of gaseous carbon source to hydrogen (C / H ratio), and the growth pressure are adjusted. The microwave power is also adjusted to control the deposition temperature and time. These parameters allow for the regulation of material growth morphology. After the deposition of the upright carbon material is complete, the plasma is turned off, and the temperature is lowered to 20–40°C. Alternatively, after deposition, the plasma can be turned off, and the electric ball valve can be adjusted to rapidly cool the sample to room temperature.
[0029] In some embodiments of the present invention, the etching gas includes hydrogen and oxygen.
[0030] In some embodiments of the present invention, step S2 includes: stopping the flow of gaseous carbon source, introducing oxygen, and performing plasma etching on the upright carbon material. The etching repair process can be achieved by adjusting the O / H ratio and controlling the plasma power to etch the disordered carbon in the upright carbon material, adjusting the etching time to reduce defects in the graphitized carbon, and simultaneously introducing oxygen defects to widen the interlayer spacing of the graphitized carbon.
[0031] In some embodiments of the present invention, in the etching process of step S2 and / or step S3, the inlet gas flow ratio of hydrogen and oxygen is 100:(1 to 300), such as 100:25, 100:50, 100:100, 100:150, etc.
[0032] In some embodiments of the present invention, the hydrogen flow rate is 50 to 200 sccm during the etching process in step S2 and / or step S3.
[0033] In some embodiments of the present invention, the oxygen flow rate in the etching process of step S2 and / or step S3 is 10 to 300 sccm.
[0034] In some embodiments of the present invention, in the etching process of step S2 and / or step S3, the plasma power during the etching process is 2 to 10 kW, such as 4.8 kW, 5.2 kW, 5.8 kW, 6.4 kW, etc.
[0035] In some embodiments of the present invention, in the etching process of step S2 and / or step S3, the etching time for each etching process is 10 to 400 s, such as 50 to 200 s.
[0036] In some embodiments of the present invention, step S2 includes: stopping the flow of gaseous carbon source, introducing oxygen, adjusting the ratio of hydrogen to oxygen (H / O ratio), controlling the plasma power, etching the disordered carbon of the upright carbon material, adjusting the etching time, and obtaining the etched upright carbon material.
[0037] In some embodiments of the present invention, in step S3, the upright carbon material obtained by etching in step S2 is subjected to repeated carbon deposition and etching processes n times to obtain the upright graphitized carbon material, where n is an integer and n≥1. By alternating carbon deposition and plasma etching repair processes, the upright height of the graphitized carbon is extended to obtain a high-load deposited two-dimensional graphitized carbon upright structure.
[0038] In some embodiments of the present invention, 100 ≥ n ≥ 1, and optionally, n can be 90, 80, 70, 60, 50, 40, 30, 20, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, etc.
[0039] In some embodiments of the present invention, 50 ≥ n ≥ 1.
[0040] In some embodiments of the present invention, 20≥n≥1, such as 4≥n≥1.
[0041] In some embodiments of the present invention, the substrate includes at least one of carbon material, conductive polymer, elemental metal, alloy material containing a single metal element, or alloy material containing multiple metal elements.
[0042] In some embodiments of the present invention, the metallic element and the metal in the metallic element are independently selected from at least one of titanium, aluminum, nickel, iron, copper, molybdenum or niobium.
[0043] In some embodiments of the present invention, the substrate comprises at least one of titanium, aluminum, nickel, stainless steel, carbon paper, iron-nickel alloy, or titanium-nickel alloy. For example, it may be at least one of titanium foil, aluminum foil, nickel foil, stainless steel, carbon paper, or iron-nickel alloy.
[0044] In some embodiments of the present invention, the preparation method further includes a step of pretreating the substrate before performing the first carbon deposition.
[0045] In some embodiments of the present invention, the pretreatment includes: placing the substrate in a cavity for vapor deposition, evacuating the cavity, introducing hydrogen and inert gas to adjust the pressure within the cavity to 0.5–5 kPa, adjusting the plasma power to 1–5 kW, and heating the substrate. By controlling the heat treatment temperature and time, impurities on the substrate surface are removed, surface smoothness is improved, the number of crystal nuclei is reduced, and it is more conducive to the formation of large-area single-crystal regions.
[0046] In some embodiments of the present invention, the inert gas includes at least one of helium, neon, argon, krypton, or xenon.
[0047] In some embodiments of the present invention, in the pretreatment step, hydrogen and inert gas are introduced to regulate the pressure inside the chamber to 0.5–2.5 kPa.
[0048] In some embodiments of the present invention, the flow rate of hydrogen in the pretreatment step is 50 to 200 sccm.
[0049] In some embodiments of the present invention, the flow rate of the inert gas in the pretreatment step is 100 to 300 sccm.
[0050] In some embodiments of the present invention, in the pretreatment step, the plasma power is adjusted to 1 to 4 kW, and then the substrate is heated.
[0051] In some embodiments of the present invention, the heating temperature of the substrate in the pretreatment step is 500-1000°C, such as 600-900°C or 800-900°C.
[0052] In some embodiments of the present invention, the heating time of the substrate in the pretreatment step is 2 to 200 min, such as 10 to 60 min or 30 to 50 min.
[0053] In some embodiments of the present invention, after pretreatment of the substrate, the introduction of inert gas into the cavity used for vapor deposition is stopped, and the upright carbon material is prepared by microwave plasma chemical vapor deposition.
[0054] In a second aspect, the present invention provides an upright graphitized carbon material prepared by the above-described preparation method.
[0055] In some embodiments of the present invention, the upright graphitized carbon material is a two-dimensional upright graphitized carbon material.
[0056] In some embodiments of the present invention, the height of the upright graphitized carbon material is 2–100 μm, such as 5–20 μm or 5–15 μm. In some embodiments of the present invention, the interlayer spacing of the upright graphitized carbon material includes… If possible The upright graphitized carbon material is an upright graphitized carbon material with a large interlayer spacing.
[0057] In some embodiments of the present invention, the diameter of the upright graphite sheets contained in the upright graphitized carbon material is 2 to 12 μm, such as 2 to 10 μm.
[0058] In some embodiments of the present invention, the thickness of the upright graphite sheets contained in the upright graphitized carbon material is 3-25 nm.
[0059] In a third aspect, the present invention provides a battery positive electrode comprising the above-described upright graphitized carbon material.
[0060] In some embodiments of the present invention, the positive electrode includes a positive electrode current collector and a carbon material layer, wherein the carbon material layer includes the upright graphitized carbon material.
[0061] In some embodiments of the present invention, the thickness ratio of the positive current collector to the carbon material layer is 1:(0.1 to 10).
[0062] In some embodiments of the present invention, the thickness of the positive current collector is 1 to 200 μm, such as 5 to 100 μm or 15 to 30 μm.
[0063] In some embodiments of the present invention, the positive current collector includes at least one of carbon material, conductive polymer, elemental metal, alloy material containing a single metal element, or alloy material containing multiple metal elements.
[0064] In some embodiments of the present invention, the metallic element and the metal in the metallic element are independently selected from at least one of titanium, aluminum, nickel, iron, copper, molybdenum or niobium.
[0065] In some embodiments of the present invention, the positive current collector includes at least one of titanium, aluminum, nickel, stainless steel, carbon paper, iron-nickel alloy, or titanium-nickel alloy. For example, it may be selected as at least one of titanium foil, aluminum foil, nickel foil, stainless steel, carbon paper, iron-nickel alloy, or titanium-nickel alloy.
[0066] In some embodiments of the present invention, the method for preparing the positive electrode includes: using a positive electrode current collector as a substrate, preparing the upright graphitized carbon material on the surface of the substrate using the method for preparing the upright graphitized carbon material according to any one of the first aspects of the present invention, thereby obtaining the positive electrode.
[0067] In a fourth aspect, the present invention provides a battery comprising the above-described upright graphitized carbon material or the above-described positive electrode.
[0068] In some embodiments of the present invention, the battery includes a dual-ion battery.
[0069] In some embodiments of the present invention, the dual-ion battery includes, but is not limited to, one or more of lithium-based dual-ion batteries, sodium-based dual-ion batteries, potassium-based dual-ion batteries, calcium-based dual-ion batteries, magnesium-based dual-ion batteries, or aluminum-based dual-ion batteries. The vertically graphitized carbon material of the present invention is used as the positive electrode material for anion storage in the dual-ion battery, resulting in a dual-ion battery with high operating voltage, excellent specific capacity, rate performance, and long-cycle stability. Optionally, the dual-ion battery includes at least one of lithium-based dual-ion batteries, sodium-based dual-ion batteries, potassium-based dual-ion batteries, calcium-based dual-ion batteries, magnesium-based dual-ion batteries, or aluminum-based dual-ion batteries.
[0070] In some embodiments of the present invention, the battery further includes a negative electrode.
[0071] In some embodiments of the present invention, the negative electrode includes at least one of lithium, sodium, potassium, calcium, or magnesium.
[0072] In some embodiments of the present invention, the battery further includes an electrolyte.
[0073] In some embodiments of the present invention, the electrolyte comprises an electrolyte and a solvent.
[0074] In some embodiments of the present invention, the concentration of the electrolyte in the electrolyte solution is 0.1 to 10 mol / L, such as 1 to 5 mol / L.
[0075] In some embodiments of the present invention, the electrolyte includes, but is not limited to, one or more of lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts, or aluminum salts.
[0076] In some embodiments of the present invention, the lithium salt includes, but is not limited to, one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, or lithium bis(trifluoromethanesulfonyl)imide.
[0077] In some embodiments of the present invention, the sodium salt includes, but is not limited to, one or more of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium difluorosulfonamide, sodium perchlorate, or sodium ditrifluoromethanesulfonamide.
[0078] In some embodiments of the present invention, the potassium salt includes, but is not limited to, one or more of potassium hexafluorophosphate, potassium tetrafluoroborate, potassium difluorosulfonylimide, potassium perchlorate, or potassium ditrifluoromethanesulfonylimide.
[0079] In some embodiments of the present invention, the calcium salt includes, but is not limited to, one or more of calcium hexafluorophosphate, calcium tetrafluoroborate, calcium bis(fluorosulfonyl)imide, calcium perchlorate, or calcium bis(trifluoromethanesulfonyl)imide.
[0080] In some embodiments of the present invention, the magnesium salt includes, but is not limited to, one or more of magnesium hexafluorophosphate, magnesium tetrafluoroborate, magnesium bis(fluorosulfonyl)imide, magnesium perchlorate, or magnesium bis(trifluoromethanesulfonyl)imide.
[0081] In some embodiments of the present invention, the selected aluminum salt includes, but is not limited to, one or more of aluminum chloride or aluminum nitrate.
[0082] In some embodiments of the present invention, the solvent includes, but is not limited to, one or more of ester solvents, ether solvents, or nitrile solvents.
[0083] In some embodiments of the present invention, the solvent includes, but is not limited to, one or more of the following: methyl ethyl carbonate, ethylene carbonate, propylene carbonate, trifluoropropylene carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, methyl formate, methyl acetate, ethyl propionate, methyl butyrate, vinyl sulfite, γ-butyrolactone, trimethyl phosphate, tetrahydrofuran, 1,3-dioxolane, 1,2-dimethoxyethylene, dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, acetonitrile, dimethyl sulfoxide, or sulfolane.
[0084] In some embodiments of the present invention, the battery further includes a separator.
[0085] In some embodiments of the present invention, the separator includes, but is not limited to, one or more of organic separators, inorganic separators, and organic-inorganic composite separators. Optionally, the separator includes, but is not limited to, glass fiber, cellulose, substituted or unsubstituted polyolefins, polyesters, etc.
[0086] In some embodiments of the present invention, the diaphragm includes, but is not limited to, one or more of the following: glass fiber membrane, polyolefin membrane, porous polyolefin membrane, polyolefin composite membrane, cellulose composite membrane, organic-inorganic composite diaphragm, nonwoven composite diaphragm, or porous composite polymer. Optionally, the polyolefin membrane includes at least one of polyvinylidene fluoride membrane, polyethylene membrane, or polypropylene membrane. Optionally, the polyolefin composite membrane includes a polyethylene / polypropylene / polypropylene composite membrane comprising a polyethylene layer, a polypropylene layer, or a polypropylene layer stacked together.
[0087] In some embodiments of the present invention, the diaphragm includes at least one of glass fiber membrane, polyvinylidene fluoride membrane, porous polyethylene membrane, porous polypropylene membrane, polyethylene / polypropylene / polypropylene composite membrane, cellulose composite membrane, porous composite polymer, organic-inorganic composite diaphragm, or nonwoven composite diaphragm.
[0088] A fifth aspect of the present invention provides an electrical device comprising the aforementioned battery, wherein the battery serves as a power source for the electrical device. Attached Figure Description
[0089] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0090] Figure 1 This is a schematic diagram of the structure of the microwave plasma vapor deposition system in an embodiment of the present invention;
[0091] Figure 2 This is a scanning electron microscope image of the upright graphitized carbon material in Embodiment 1 of the present invention;
[0092] Figure 3 This is a transmission electron microscope (TEM) image of the upright graphitized carbon material in Example 1 of the present invention;
[0093] Figure 4 This is the Raman spectrum of the upright graphitized carbon material in Example 1 of the present invention;
[0094] Figure 5 This is a charge-discharge curve of the dual-ion battery in Embodiment 1 of the present invention;
[0095] Figure 6 This is a graph showing the long-cycle performance of the dual-ion battery in Example 1 of the present invention at a current density of 1000 mA / g.
[0096] Reference numerals: 1. Microwave source and control cabinet; 2. Electric three-pin adjuster; 3. Transition waveguide section; 4. Coupled waveguide and reaction cavity; 5. Discharge cavity; 6. Gas control system; 7. Plasma; 8. Sample product; 9. Substrate stage; 10. Heating stage; 11. Vacuum pumping and measurement and control system; 12. Sample stage adjuster. Detailed Implementation
[0097] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0098] Unless otherwise specified, the experimental methods described in the following examples are generally performed under conventional conditions in the art or as recommended by the manufacturer; the raw materials and reagents used are all commercially available from the conventional market unless otherwise specified.
[0099] The microwave plasma vapor deposition system used in this embodiment of the invention can be selected from commercially available microwave plasma vapor deposition systems from the conventional market, or a system with a structural schematic diagram as shown in the attached figure can be used. Figure 1 The 10kW-class microwave plasma vapor deposition system is shown.
[0100] Example 1
[0101] This embodiment discloses a spatially ordered two-dimensional upright graphitized carbon material, the preparation process of which includes:
[0102] (I) Pretreatment: The titanium foil substrate was cut into 10mm×10mm pieces and ultrasonically treated in deionized water, ethanol, and acetone for 10 minutes in sequence to clean the substrate, followed by drying. The cleaned substrate was placed in the sample stage of the microwave plasma vapor deposition system. After closing the chamber, the vacuum pump was turned on to evacuate to a pressure of 0.1Pa. H2 and Ar were introduced, with H2 and Ar flow rates of 100sccm and 200sccm, respectively. The substrate was heated by the coupling effect between the plasma and the substrate. The plasma power was adjusted to 4kW and the pressure to 1.5kPa, and the temperature was controlled at 800℃ for 30 minutes.
[0103] (II) Carbon deposition: The Ar gas source was turned off, the H2 gas source flow rate was adjusted, and acetylene was introduced into the cavity as the carbon source gas. The flow rates of H2 and acetylene were controlled at 200 sccm and 100 sccm, respectively. The reaction temperature was maintained at 800℃, the microwave power (plasma power) was 5.8kW, and the pressure was increased to 7kPa. After reacting for 30min, the plasma was quickly turned off, allowing the sample to cool to room temperature within 10min, forming a two-dimensional graphitized carbon vertical structure.
[0104] (III) Etching Repair: After deposition, the carbon source gas is turned off, the H2 gas source flow rate is adjusted to 100 sccm, and O2 is introduced into the cavity at a flow rate of 50 sccm. Etching repair is then carried out using hydrogen / oxygen plasma for 150 s.
[0105] (Ⅳ) Cyclic carbon deposition / etching: Repeat the above carbon deposition and etching repair process 3 times (that is, alternate carbon deposition and etching repair 3 times) to obtain two-dimensional upright graphitized carbon material grown on the substrate surface. Then the sample is taken out, where the thickness of the substrate is 25 μm.
[0106] This embodiment also provides a positive electrode sheet, including the substrate used in this embodiment and the two-dimensional vertical graphitized carbon material grown on the surface of the substrate, wherein the two-dimensional vertical graphitized carbon material serves as a carbon material layer and the substrate serves as a positive electrode current collector.
[0107] This embodiment also provides a dual-ion battery, including the positive electrode sheet of this embodiment, the preparation process of which includes:
[0108] (1) Preparation of positive electrode sheet: Take the positive electrode sheet of this embodiment directly and cut it into a circular sheet with a diameter of 10mm for later use.
[0109] (2) Preparation of negative electrode sheet: Cut the sealed lithium metal strip into round pieces with a diameter of 12mm in the glove box, and gently flatten them in a plastic bag for later use.
[0110] (3) Preparation of diaphragm: Cut the glass fiber diaphragm into circles with a diameter of 16 mm, and dry them thoroughly in an oven before use.
[0111] (4) Preparation of electrolyte: Take 2 mL of ethyl methyl carbonate (EMC) with a pipette, weigh 1.22 g of LiPF6, mix them, and stir for 6 h until they are fully dissolved to obtain electrolyte (4 mol / L LiPF6 / EMC) for later use.
[0112] (5) Battery assembly: This step is carried out in a glove box filled with argon gas. The positive electrode, separator, electrolyte and negative electrode are placed in sequence. After the electrolyte fully wets the separator, the battery is packaged to obtain a dual-ion battery.
[0113] Examples 2-12
[0114] Examples 2-12 disclose a series of two-dimensional vertical graphitized carbon materials, which differ from Example 1 in that the substrate material and / or substrate thickness are different, while the other experimental parameters are consistent with the steps in Example 1. The substrates in Examples 2-12 are detailed in Table 1 below.
[0115] Examples 2 through 12 also disclose a series of positive electrode sheets, which differ from Example 1 only in that the positive electrode sheets of Examples 2 through 12 respectively include the substrate used in Examples 2 through 12 and the two-dimensional vertical graphitized carbon material grown on the surface of the corresponding substrate. For example, the positive electrode sheet disclosed in Example 2 differs from that of Example 1 only in that the carbon material layer of the positive electrode sheet in Example 2 is the two-dimensional vertical graphitized carbon material obtained in Example 2, and the positive current collector is the substrate used in Example 2 for growing the two-dimensional vertical graphitized carbon material.
[0116] Examples 2 to 12 also disclose a series of dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Examples 2 to 12 adopts the positive electrode sheet of Examples 2 to 12 respectively.
[0117] Examples 13-18
[0118] Examples 13-18 disclose a series of two-dimensional vertical graphitized carbon materials, which differ from Example 1 in that the temperature and / or time of the pretreatment process are different, while the other experimental parameters are consistent with the steps in Example 1. The temperature and time of the pretreatment process in Examples 13-18 are detailed in Table 2 below.
[0119] Examples 13 to 18 also disclose a series of positive electrode sheets, which differ from Example 1 only in that the positive electrode sheets of Examples 13 to 18 respectively correspond to the substrate used in Examples 13 to 18 and the vertical graphitized carbon material grown on the surface of the corresponding substrate.
[0120] Examples 13 to 18 also disclose a series of dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Examples 13 to 18 adopts the positive electrode sheet of Examples 13 to 18 respectively.
[0121] Examples 19-22
[0122] Examples 19-22 disclose a series of two-dimensional upright graphitized carbon materials, which differ from Example 1 in that the plasma power in the pretreatment process is different, while the other experimental parameters are consistent with the steps in Example 1. The plasma power in the pretreatment process of Examples 19-22 is detailed in Table 3 below.
[0123] Examples 19 to 22 also disclose a series of positive electrode sheets, which differ from Example 1 only in that the positive electrode sheets of Examples 19 to 22 respectively correspond to the substrate used in Examples 19 to 22 and the vertical graphitized carbon material grown on the surface of the corresponding substrate.
[0124] Examples 19-22 also disclose a series of dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Examples 19-22 adopts the positive electrode sheet of Examples 19-22 respectively.
[0125] Examples 23-26
[0126] Examples 23-26 disclose a series of two-dimensional upright graphitized carbon materials, which differ from Example 1 in that the pretreatment pressure is different, while the other experimental parameters are consistent with the steps in Example 1. The pretreatment pressures in Examples 23-26 are detailed in Table 4 below.
[0127] Examples 23 to 26 also disclose a series of positive electrode sheets, which differ from Example 1 only in that the positive electrode sheets of Examples 23 to 26 respectively correspond to the substrate used in Examples 23 to 26 and the vertical graphitized carbon material grown on the surface of the corresponding substrate.
[0128] Examples 23 to 26 also disclose a series of dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Examples 23 to 26 adopts the positive electrode sheet of Examples 23 to 26 respectively.
[0129] Examples 27-29
[0130] Examples 27-29 disclose a series of two-dimensional upright graphitized carbon materials, which differ from Example 1 in that the types of carbon sources are different, while the other experimental parameters are consistent with the steps in Example 1. The carbon sources in Examples 27-29 are detailed in Table 5 below.
[0131] Examples 27 to 29 also disclose a series of positive electrode sheets, which differ from Example 1 only in that the positive electrode sheets of Examples 27 to 29 respectively correspond to the substrate used in Examples 27 to 29 and the vertical graphitized carbon material grown on the surface of the corresponding substrate.
[0132] Examples 27 to 29 also disclose a series of dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Examples 27 to 29 adopts the positive electrode sheet of Examples 27 to 29 respectively.
[0133] Examples 30-32
[0134] Examples 30-32 disclose a series of two-dimensional upright graphitized carbon materials, which differ from Example 1 in that the ratio of carbon source to hydrogen in the carbon deposition is different, while the other experimental parameters are consistent with the steps in Example 1. Details of the carbon source and hydrogen in Examples 30-32 are shown in Table 6 below.
[0135] Examples 30-32 also disclose a series of positive electrode sheets, which differ from Example 1 only in that the positive electrode sheets of Examples 30-32 respectively correspond to the substrate used in Examples 30-32 and the vertical graphitized carbon material grown on the surface of the corresponding substrate.
[0136] Examples 30-32 also disclose a series of dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Examples 30-32 adopts the positive electrode sheet of Examples 30-32 respectively.
[0137] Examples 33-36
[0138] Examples 33-36 disclose a series of two-dimensional upright graphitized carbon materials, which differ from Example 1 in that the microwave power during carbon deposition is different, while the other experimental parameters are consistent with the steps in Example 1. The microwave power in Examples 33-36 is detailed in Table 7 below.
[0139] Examples 33 to 36 also disclose a series of positive electrode sheets, which differ from Example 1 only in that the positive electrode sheets of Examples 33 to 36 respectively correspond to the substrate used in Examples 33 to 36 and the vertical graphitized carbon material grown on the surface of the corresponding substrate.
[0140] Examples 33 to 36 also disclose a series of dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Examples 33 to 36 adopts the positive electrode sheet of Examples 33 to 36 respectively.
[0141] Examples 37-45
[0142] Examples 37-45 disclose a series of two-dimensional upright graphitized carbon materials, which differ from Example 1 in that the growth temperature, growth pressure, and growth time during carbon deposition are different, while the other experimental parameters are consistent with the steps in Example 1. Details of the growth temperature, growth pressure, and growth time in Examples 37-45 are shown in Table 8 below.
[0143] Examples 37 to 45 also disclose a series of positive electrode sheets, which differ from Example 1 only in that the positive electrode sheets of Examples 37 to 45 respectively correspond to the substrate used in Examples 37 to 45 and the vertical graphitized carbon material grown on the surface of the corresponding substrate.
[0144] Examples 37-45 also disclose a series of dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Examples 37-45 adopts the positive electrode sheet of Examples 37-45 respectively.
[0145] Examples 46-51
[0146] Examples 46-51 disclose a series of two-dimensional upright graphitized carbon materials, which differ from Example 1 in that the hydrogen-oxygen ratio and / or processing time in the etching repair process are different, while the other experimental parameters are consistent with the steps in Example 1. Details of the hydrogen-oxygen ratio and processing time in Examples 46-51 are shown in Table 9 below.
[0147] Examples 46 to 51 also disclose a series of positive electrode sheets, which differ from Example 1 only in that the positive electrode sheets of Examples 46 to 51 respectively correspond to the substrate used in Examples 46 to 51 and the vertical graphitized carbon material grown on the surface of the corresponding substrate.
[0148] Examples 46-51 also disclose a series of dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Examples 46-51 adopts the positive electrode sheet of Examples 46-51 respectively.
[0149] Examples 52-56
[0150] Examples 52-56 disclose a series of two-dimensional upright graphitized carbon materials, which differ from Example 1 in that the number of cyclic deposition / etching is different, while the other experimental parameters are consistent with the steps in Example 1. The number of cyclic deposition / etching in Examples 52-56 is detailed in Table 10 below.
[0151] Examples 52 to 56 also disclose a series of positive electrode sheets, which differ from Example 1 only in that the positive electrode sheets of Examples 52 to 56 respectively correspond to the substrate used in Examples 52 to 56 and the vertical graphitized carbon material grown on the surface of the corresponding substrate.
[0152] Examples 52-56 also disclose a series of dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Examples 52-56 adopts the positive electrode sheet of Examples 52-56 respectively.
[0153] Examples 57-61
[0154] Examples 57-61 also disclose a series of dual-ion batteries, which differ from the dual-ion battery of Example 1 only in that the negative electrode material and electrolyte are different, while the other experimental parameters are consistent with the steps in Example 1. The negative electrode material and electrolyte of Examples 57-61 are detailed in Table 11 below.
[0155] Examples 62-65
[0156] Examples 62-65 also disclose a series of dual-ion batteries, which differ from the dual-ion battery of Example 1 only in the concentration of LiPF6 in the electrolyte; all other experimental parameters are consistent with the steps in Example 1. The electrolyte concentrations in Examples 62-65 are detailed in Table 12 below.
[0157] Examples 66-85
[0158] Examples 66-85 also disclose a series of dual-ion batteries, which differ from the dual-ion battery of Example 1 only in the type of electrolyte salt in the electrolyte and the material of the negative electrode; all other experimental parameters are the same as those in Example 1. Details of the electrolyte salt and negative electrode in Examples 66-85 are shown in Table 13 below.
[0159] Examples 86-109
[0160] Examples 86-109 also disclose a series of dual-ion batteries, which differ from the dual-ion battery of Example 1 only in the type of solvent in the electrolyte; all other experimental parameters are consistent with the steps in Example 1. Details of the electrolyte solvents in Examples 86-109 are shown in Table 14 below.
[0161] Examples 110-117
[0162] Examples 110-117 also disclose a series of dual-ion batteries, which differ from the dual-ion battery of Example 1 only in that the separator material is different; all other experimental parameters are the same as those in Example 1. Details of the separators used in Examples 110-117 are shown in Table 15 below.
[0163] Example 118
[0164] This embodiment discloses a series of electrical devices, which respectively correspond to the dual-ion batteries in embodiments 1 to 117, and the power supply of the dual-ion batteries for the electrical devices.
[0165] Comparative Example 1
[0166] This comparative example discloses a positive electrode sheet of two-dimensional vertical graphitized carbon material. The difference between this example and Example 1 is that no etching process is performed, and all other experimental parameters are consistent with the steps in Example 1.
[0167] This comparative example also discloses a dual-ion battery, which differs from Example 1 only in that the positive electrode of the dual-ion battery in this comparative example uses the positive electrode sheet of this comparative example.
[0168] Comparative Examples 2-3
[0169] Comparative Examples 2 and 3 disclose positive electrode sheets containing different graphitized carbon materials, which differ from Example 1 in that the crystal structures of the carbon materials are different. The crystal structures of Comparative Examples 2 and 3 are detailed in Table 17 below.
[0170] Comparative Examples 2 and 3 also disclose dual-ion batteries, which differ from Example 1 only in that the positive electrode of the dual-ion batteries in Comparative Examples 2 and 3 adopts the positive electrode sheet of Comparative Examples 2 and 3 respectively.
[0171] Test case
[0172] This experimental example demonstrates the performance testing of the upright graphitized carbon materials and dual-ion batteries of each embodiment, specifically including:
[0173] 1. For example Figure 2The images shown are scanning electron microscope (SEM) images of the upright graphitized carbon material in Example 1, where Figure (a) is a top view and Figure (b) is a cross-sectional view. These images reveal that the upright graphitized carbon material possesses a distinct two-dimensional nanosheet structure with wrinkled tips, providing more anion intercalation sites and contributing to increased ion storage capacity. The nanosheets are approximately 5-10 μm in diameter and grow upright on the substrate, with a growth height of approximately 10 μm. This not only provides vertical nanochannels, which is beneficial for improving anion diffusion kinetics, but also buffers anion intercalation expansion, enhancing structural stability. Furthermore, the higher loading capacity is more conducive to the industrial application of the material (such as its potential application in dual-ion batteries).
[0174] like Figure 3 The image shown is a transmission electron microscope (TEM) image of the upright graphitized carbon material in Example 1. It exhibits a locally ordered graphitized structure accompanied by disordered carbon structures. This is mainly because the introduction of impurity oxygen not only replaces some of the graphitized carbon, causing local lattice expansion and thus increasing the interlayer spacing, but also eliminates excessive disordered carbon structures, promoting the ordered growth of graphitized carbon. Its ordered graphitized carbon structure facilitates the directional transport of anions along the ordered structure. Simultaneously, its interlayer spacing is... Larger interlayer spacing than traditional graphite This is beneficial for improving anion diffusion and intercalation kinetics, thereby improving the rate performance of the battery.
[0175] like Figure 4 The image shown is the Raman spectrum of the upright graphitized carbon material in Example 1. It can be seen that at 1350 cm⁻¹... -1 The peak at 1580 cm⁻¹ corresponds to disordered carbon (D peak), indicating the presence of defects and abundant open edges in the sample. -1 The peak at the location corresponds to graphitized carbon (G peak), indicating the existence of an ordered graphite structure. This is mainly because the etching process eliminates some disordered carbon and introduces active oxygen defects, which is beneficial to improving the intercalation and deintercalation performance of anions.
[0176] 2. Performance testing of various dual-ion batteries
[0177] 1) The test method includes: using the dual-ion battery of Example 1, conducting charge-discharge tests at a high rate of 1000mA / g within a voltage range of 2–4.8V, such as... Figure 5 As shown, the dual-ion battery of Example 1 has a charge specific capacity of 161 mAh / g and a discharge specific capacity of 158 mAh / g. Figure 6 As shown, the dual-ion battery of Example 1 retains ≥80% capacity after 2750 charge-discharge cycles.
[0178] 2) The dual-ion batteries of each embodiment and comparative example were charged and discharged at a rate of 500 mA / g within a voltage range of 2–4.8V. The resulting discharge specific capacity and the number of cycles when the capacity retention reached 80% were recorded in the following tables:
[0179] Table 1. Performance test results of lithium dual-ion batteries for carbon material samples obtained from different substrates.
[0180] Example base Substrate thickness Specific capacity (mAh / g) Loop count Example 1 Titanium foil 25μm 171 1308 Example 2 Titanium foil 20μm 164 1203 Example 3 Titanium foil 30μm 158 1258 Example 4 Nickel foil 20μm 155 1035 Example 5 Nickel foil 25μm 164 1203 Example 6 Nickel foil 30μm 153 1150 Example 7 Aluminum foil 15μm 159 1134 Example 8 Aluminum foil 20μm 168 1301 Example 9 Aluminum foil 25μm 153 1241 Example 10 304 stainless steel 25μm 165 1025 Example 11 Carbon paper 25μm 142 1265 Example 12 Iron-nickel alloy (4J50) 25μm 153 1280
[0181] As shown in Table 1, the lithium dual-ion batteries in the above embodiments all exhibit high discharge specific capacity and cycle stability. Among them, when a 25μm titanium foil is used as the substrate, the grown two-dimensional graphitized carbon vertical structure shows the best energy storage performance, with the highest specific capacity and the best cycle performance. This may be because titanium foil has better compatibility and lattice fit with graphitized carbon materials, which is more conducive to carbon material deposition.
[0182] Table 2. Performance test results of lithium dual-ion batteries for carbon material samples obtained at different pretreatment temperatures and times.
[0183] Example Pretreatment temperature Preprocessing time Specific capacity (mAh / g) Loop count Example 1 800℃ 30min 171 1308 Example 13 600℃ 30min 151 1263 Example 14 700℃ 30min 163 1296 Example 15 900℃ 30min 169 1327 Example 16 800℃ 10min 163 1206 Example 17 800℃ 50min 169 1312 Example 18 800℃ 60min 170 1298
[0184] As shown in Table 2, compared to Examples 13-18, the two-dimensional graphitized carbon upright structure grown in Example 1, with a pretreatment temperature of 800℃ and a pretreatment time of 30 min, exhibited the best performance in terms of energy storage capacity and stability. This may be because, compared to lower heat treatment temperatures and shorter heat treatment times, the pretreatment in Example 1 better removed impurities and oxides from the substrate surface, making the growth of upright graphite less restricted and thus improving the energy storage performance of the resulting battery; and compared to higher heat treatment temperatures and longer treatment times, the pretreatment in Example 1 was more energy-efficient.
[0185] Table 3. Performance test results of lithium dual-ion batteries for carbon material samples obtained with different pretreatment plasma powers.
[0186] Example Pretreatment plasma power (kW) Specific capacity (mAh / g) Loop count Example 1 4 171 1308 Example 19 1 139 1203 Example 20 2 157 1217 Example 21 3 163 1234 Example 22 5 162 1195
[0187] As can be seen from Table 3, compared with Examples 19-22, the plasma power in the pretreatment process of Example 1 was adjusted to 4kW, and the prepared upright graphite exhibited the best performance in terms of energy storage capacity and stability. Among them, compared with the higher pretreatment plasma power in Example 22, the pretreatment plasma power in Example 1 resulted in better substrate lattice integrity and improved the lattice matching between the substrate and the graphite carbon material.
[0188] Table 4. Performance test results of lithium dual-ion batteries for carbon material samples obtained under different pretreatment pressures.
[0189] Example Pretreatment pressure Specific capacity (mAh / g) Loop count Example 1 1.5 kPa 171 1308 Example 23 0.5 kPa 134 1033 Example 24 1kPa 159 1139 Example 25 2.5kPa 163 1036 Example 26 5kPa 142 954
[0190] As can be seen from Table 4, compared with Examples 23-26, the upright graphite prepared in Example 1 with a pressure adjustment of 1.5 kPa during the pretreatment process exhibits the best performance in terms of energy storage capacity and stability. Specifically, compared with Example 26, the lower pressure in Example 1 is less likely to reduce the plasma generation density and thus affect graphite carbon deposition.
[0191] Table 5. Performance test results of lithium dual-ion batteries for carbon material samples obtained under different carbon sources.
[0192]
[0193] As shown in Table 5, compared to Examples 27-29, the two-dimensional graphitized carbon vertical structure grown from acetylene in Example 1 exhibits the best performance in terms of energy storage capacity and stability. This is because acetylene more readily generates C2 active particles for carbon deposition, resulting in a higher sample height and less disordered carbon, which is more conducive to improving energy storage performance.
[0194] Table 6. Performance test results of lithium dual-ion batteries for carbon material samples with different H2 / C2H2 ratios.
[0195]
[0196]
[0197] As shown in Table 6, compared to Examples 30-32, the H2 to C2H2 flow ratio of 200:100 in Example 1 resulted in the best performance in terms of energy storage capacity and stability for the grown two-dimensional graphitized carbon upright structure. Compared to Examples 30 and 32, Example 1 had a higher carbon source ratio, resulting in higher graphitized carbon yield and a more pronounced upright structure, thus achieving a higher capacity. Compared to Example 31, Example 1 had a relatively lower carbon source ratio, making the upright morphology of the graphitized carbon less prone to dendrite formation, leading to larger channel sizes and less susceptibility to blockage, which is beneficial for large-capacity anion storage.
[0198] Table 7. Performance test results of lithium-based dual-ion batteries obtained from carbon material samples with different microwave powers.
[0199]
[0200] As shown in Table 7, compared to Examples 33-36, the two-dimensional graphitized carbon upright structure grown in Example 1 exhibits the best performance in terms of energy storage capacity and stability when the microwave power during the deposition process is 5.8 kW. Compared to Examples 33-34, Example 1 has a higher microwave power, resulting in faster graphitized carbon growth, a higher growth height, and a higher ion storage density. Compared to Examples 35-36, the lower power in Example 1 leads to smaller disordered defect structures, thereby improving its energy storage capacity and stability.
[0201] Table 8. Performance test results of lithium-based dual-ion batteries obtained from carbon material samples at different carbon deposition temperatures, pressures, or times.
[0202]
[0203]
[0204] As shown in Table 8, compared to Examples 37-45, the two-dimensional graphitized carbon vertical structure grown in Example 1, with a deposition temperature of 800℃, a pressure of 7 kPa, and a time of 30 min, exhibited the best performance in terms of energy storage capacity and stability. This may be because: compared to lower deposition temperatures, lower pressures, or shorter growth times, Example 1 resulted in a higher proportion of graphitized carbon, and compared to higher deposition temperatures, higher pressures, or longer growth times, it was less likely to form dense graphitized carbon dendrites, thus leading to superior capacity and cycle performance.
[0205] Table 9. Performance test results of lithium-based dual-ion batteries obtained from carbon material samples with different H / O ratios or etching times.
[0206] Example <![CDATA[H2 flow rate (sccm)]]> <![CDATA[O2 flow rate (sccm)]]> Time (s) <![CDATA[I D / I G ]]> Specific capacity (mAh / g) Loop count Example 1 100 50 150 0.89 171 1308 Example 46 100 25 150 0.96 167 1236 Example 47 100 100 150 0.95 159 1253 Example 48 100 150 150 1.03 142 1268 Example 49 100 50 50 0.98 158 1262 Example 50 100 50 100 0.94 163 1286 Example 51 100 50 200 0.97 169 1296
[0207] As shown in Table 9, compared to Examples 46-51, the carbon material obtained in Example 1, with a H2 to O2 flow ratio of 100:50 and an etching time of 150 s, exhibited the best energy storage performance. This is likely because, compared to Examples 46-49, the introduction of a more appropriate amount of oxygen in Example 1 better eliminated the disordered carbon structure. Furthermore, the introduced impurity oxygen improved the π-π stacking interaction of the graphitized carbon layers, widened the interlayer spacing, and thus enhanced the anion intercalation kinetics and stability.
[0208] Table 10 Performance test results of lithium-based dual-ion batteries obtained from carbon material samples with different deposition / etching cycles.
[0209]
[0210] As shown in Table 10, compared to Examples 52-56, Example 1, with 3 cycles of deposition / etching and an upright graphitized carbon height of 10 μm, exhibited the best energy storage performance. This is likely because multiple cycles of deposition / etching can correct the upright structure of the two-dimensional graphitized carbon. Compared to Examples 52-53, Example 1 had a higher number of cycles, resulting in a higher density of active sites and higher capacity. Compared to Examples 54-56, and especially compared to Examples 55-56, the higher number of cycles in Example 1 made it less prone to forming closed dendrites at the material tip, thus reducing the likelihood of dendrite formation and promoting anion storage.
[0211] Table 11 Performance test results of dual-ion batteries with different metal systems
[0212]
[0213] As an example, 1mol / L NaPF6-EMC in the table refers to an electrolyte containing 1mol / L NaPF6 in EMC; the meanings for other electrolytes are similar.
[0214] As can be seen from Table 11, when the negative electrode uses metals such as sodium, potassium, calcium, magnesium and aluminum and their corresponding salts as electrolytes, the positive electrode material exhibits good anion storage performance. Therefore, it can be used as the positive electrode material for lithium, sodium, potassium, calcium, magnesium and aluminum-based dual-ion batteries. Among them, lithium-ion diffusion kinetics are better than those of sodium, potassium, calcium, magnesium and aluminum ions, so lithium-based dual-ion batteries have better performance.
[0215] Table 12 Performance test results of lithium-based dual-ion batteries under different electrolyte concentrations
[0216] Example <![CDATA[Concentration of LiPF6 in electrolyte]]> Specific capacity (mAh / g) Loop count Example 1 4mol / L 171 1308 Example 62 1mol / L 155 1236 Example 63 2mol / L 163 1264 Example 64 3mol / L 168 1278 Example 65 5mol / L 164 1296
[0217] As shown in Table 12, compared to Examples 62-64, the lithium-based dual-ion battery assembled using a 4 mol / L LiPF6-EMC electrolyte in Example 1 exhibits the best performance. It can be seen that with increasing electrolyte concentration, cycle life and capacity initially increase slowly, reaching their peak performance at 4 mol / L. Specifically, compared to Example 65, the electrolyte in Example 1 results in lower electrolyte viscosity, increasing ion migration rate and thus improving performance.
[0218] Table 13 Performance test results of dual-ion batteries under different metal electrolyte salts
[0219]
[0220]
[0221] As shown in Table 13, compared to Examples 66-85, the dual-ion battery assembled in Example 1, using lithium metal as the negative electrode and LiPF6 as the electrolyte salt, exhibits the highest specific capacity and best cycle performance. It can be seen that compared to cases with smaller anion sizes, the anions in Example 1 are less prone to strong solvation, and desolvation is easier, allowing the anions to more easily enter the graphitized carbon. Compared to cases with larger anion sizes, the anions in Example 1 are more easily inserted into the graphitized carbon, resulting in stronger battery performance. Furthermore, because lithium-ion diffusion kinetics are superior to those of sodium, potassium, calcium, magnesium, and aluminum ions, the lithium-based dual-ion battery performs better.
[0222] Table 14 Performance test results of lithium-based dual-ion batteries under different electrolyte solvents
[0223]
[0224]
[0225] As can be seen from Table 14, compared with Examples 86-109, the lithium-based dual-ion battery assembled in Example 1, which used ethyl methyl carbonate as the electrolyte solvent, had the highest specific capacity and the best cycle performance.
[0226] Table 15 Performance test results of lithium-based dual-ion batteries with different separators
[0227] Example diaphragm Specific capacity (mAh / g) Loop count Example 1 Fiberglass membrane 171 1308 Example 110 polyvinylidene fluoride membrane 168 1296 Example 111 Porous polyethylene film 163 1286 Example 112 Porous polypropylene membrane 165 1283 Example 113 Polyethylene / polypropylene / polypropylene composite film 170 1290 Example 114 Cellulose composite membrane 160 1269 Example 115 Porous composite polymers 169 1299 Example 116 Organic-inorganic composite membrane 170 1304 Example 117 Non-woven composite membrane 161 1203
[0228] As can be seen from Table 15, compared with Examples 110-117, the membrane used in Example 1 is a glass fiber membrane, and the assembled dual-ion battery has the highest specific capacity and the best cycle performance, possibly because its ion transport channel is more conducive to the diffusion of large-size anions.
[0229] Table 16 Comparison of Lithium-ion Battery Performance Test Results for Carbon Material Samples Prepared Without Etching Treatment
[0230]
[0231] As can be seen from Table 16, the samples without etching exhibit poor energy storage performance. This may be because the carbon deposition process not only seals the interlayer openings but also results in smaller interlayer ion channels, limiting anion intercalation kinetics and stability.
[0232] Table 17 Performance test results of lithium dual-ion batteries for carbon material samples with different crystal structures.
[0233]
[0234]
[0235] As shown in Table 17, samples with different crystal structures exhibit varying energy storage performance, with the locally graphitized structure showing the best performance. This may be because locally graphitized structures expose more active sites for anion intercalation, while non-graphitized structures can buffer the sample volume expansion caused by anion intercalation, thereby improving stability.
[0236] In summary, this invention provides a method for in-situ growth of two-dimensional graphitized carbon upright structures on a substrate (current collector) using microwave plasma chemical vapor deposition. By studying process conditions such as carbon source, H / C ratio, growth power, substrate and substrate temperature, pressure, and reaction time, spatially ordered two-dimensional graphitized carbon upright structures can be grown in a controllable manner to improve its anion storage performance. In the electrode fabrication process of this invention, the introduction of inactive conductive agents and binders can be avoided (gas-free materials), which is beneficial for improving energy density and power density. Furthermore, it brings the advantage of lower substrate contact resistance, thus improving kinetic performance. The positive electrode in this invention contains vertically graphitized carbon material. The vertically open structure of the carbon material guides the transport of anions and electrons by shortening the lengthy charge carrier transport path, which is beneficial to improving mass and charge transfer behavior. The large interlayer spacing of the vertically graphitized carbon material can reduce the anion diffusion barrier, further improving the kinetic performance, thereby solving the problem of slow mass and charge transfer kinetics and achieving fast charging performance of the battery. At the same time, the ordered spatial structure of the vertically graphitized carbon material can accommodate the anion intercalation expansion, enhance structural stability, and achieve long cycle life performance of the battery.
[0237] Unless otherwise specified, the term "about" in this invention actually means that the allowable error is within ±2%, for example, about 100 is actually 100 ± 2% × 100. The terms "room temperature" and "room temperature" in this invention, unless otherwise specified, are approximately 20 to 30°C. The phrase "between..." in this invention includes the number itself; for example, "between 2 and 3" includes the endpoints 2 and 3.
[0238] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments, and various changes can be made within the scope of knowledge possessed by those skilled in the art without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A method for preparing an upright graphitized carbon material, characterized in that, The preparation method includes the following steps: S1, using raw material I containing a gaseous carbon source, vertical carbon materials are prepared by carbon deposition on the substrate surface through microwave plasma chemical vapor deposition. S2, the upright carbon material is subjected to plasma etching treatment using etching gas; S3, repeat steps S1 and S2 to obtain the upright graphitized carbon material; The gaseous carbon source includes at least one of methane, ethylene, acetylene, or carbon dioxide; The raw material I for preparation also includes hydrogen; In step S1 and / or step S3, during the carbon deposition process, the inlet gas flow ratio of hydrogen to gaseous carbon source is 200:(50~200). In step S1 and / or step S3, the microwave power is 5~15kW during the carbon deposition process; During the carbon deposition process in step S1 and / or step S3, the growth temperature of the upright carbon material is 400~1100℃; During the carbon deposition process in step S1 and / or step S3, the growth pressure of the upright carbon material is 2~12 kPa; In the carbon deposition process described in step S1 and / or step S3, the growth time of the upright carbon material is 2 to 200 min; In the etching process in step S2 and / or step S3, the etching gas includes hydrogen and oxygen, and the inlet gas flow ratio of hydrogen and oxygen is 100:(25~150). In the etching process described in step S2 and / or step S3, the plasma power during the etching process is 2~10kW; In the etching process described in step S2 and / or step S3, the etching time for each etching process is 10 to 400 seconds. The interlayer spacing of the upright graphitized carbon material is 3.57~3.60 Å; The upright graphitized carbon material is a two-dimensional upright graphitized carbon material. The height of the upright graphitized carbon material is 2~100μm; The diameter of the upright graphite flakes contained in the upright graphitized carbon material is 2~12μm.
2. The method for preparing the upright graphitized carbon material according to claim 1, characterized in that, In step S3, the upright carbon material obtained by etching in step S2 is subjected to carbon deposition and etching processes n times to obtain the upright graphitized carbon material, where n is an integer and n≥1.
3. The method for preparing the upright graphitized carbon material according to claim 2, characterized in that, 100≥n≥1。 4. The method for preparing the upright graphitized carbon material according to claim 1, characterized in that, The substrate includes at least one of carbon materials, conductive polymers, elemental metals, alloys containing a single metal element, or alloys containing multiple metal elements.
5. The method for preparing the upright graphitized carbon material according to claim 4, characterized in that, The metallic element and the metal in the metallic element are independently selected from at least one of titanium, aluminum, nickel, iron, copper, molybdenum or niobium.
6. The method for preparing the upright graphitized carbon material according to claim 4, characterized in that, The substrate includes at least one of titanium, aluminum, nickel, stainless steel, carbon paper, iron-nickel alloy, or titanium-nickel alloy.
7. The method for preparing the upright graphitized carbon material according to claim 4, characterized in that, The preparation method also includes a step of pretreating the substrate before the first carbon deposition.
8. The method for preparing the upright graphitized carbon material according to claim 7, characterized in that, The pretreatment includes: placing the substrate in a cavity for vapor deposition, evacuating the cavity, introducing hydrogen and inert gas to adjust the pressure inside the cavity to 0.5~5 kPa, adjusting the plasma power to 1~5 kW, and heating the substrate.
9. The method for preparing the upright graphitized carbon material according to claim 7, characterized in that, In the pretreatment step, the heating temperature of the substrate is 500~1000.
10. The method for preparing the upright graphitized carbon material according to claim 7, characterized in that, In the pretreatment step, the heating time of the substrate is 2 to 200 minutes.
11. An upright graphitized carbon material, characterized in that, It is prepared by the method described in any one of claims 1 to 10.
12. A battery positive electrode, characterized in that, The material includes the upright graphitized carbon material prepared by the method according to any one of claims 1 to 8 or the upright graphitized carbon material according to claim 11.
13. A battery, characterized in that, The invention includes the vertically graphitized carbon material prepared by the method according to any one of claims 1 to 10, the vertically graphitized carbon material according to claim 11, or the positive electrode according to claim 12.
14. The battery according to claim 13, characterized in that, The battery includes a dual-ion battery.
15. An electrical appliance, characterized in that, Includes the battery as described in claim 13 or 14, wherein the battery is used as a power source for the electrical device.
Citation Information
Patent Citations
Method for continuously preparing graphene powder in bulk
CN110451496A
Preparation method of three-dimensional vertical graphene
CN112047327A
